Considerations when treating high-grade pediatric glioma patients with immunotherapy. (1st February 2021) - Crotty, Erin; Downey, Kira; Ferrerosa, Lauren; Flores, Catherine; Hegde, Bindu; Raskin, Scott; Hwang, Eugene; Vitanza, Nicholas; Okada, Hideho
ABSTRACT: Introduction: Children with high-grade gliomas (pHGGs) represent a clinical population in substantial need of new therapeutic options given the inefficacy and toxicity of current standard-of-care modalities. Although immunotherapy has emerged as a promising modality, it has yet to elicit a significant survival benefit for pHGG patients. While preclinical studies address a variety of underlying challenges, translational clinical trial design and management also need to reflect the most updated progress and lessons from the field. Areas Covered: The authors will focus our discussion on the design of clinical trials, the management of potential toxicities, immune monitoring, and novel biomarkers. Clinical trial design should integrate appropriate patient populations, novel, and preclinically optimized trial design, and logical treatment combinations, particularly those which synergize with standard of care modalities. However, there are caveats due to the nature of immunotherapy trials, such as patient selection bias, evidenced by the frequent exclusion of patients on high-dose corticosteroids. Robust immune-modulating effects of modern immunotherapy can have toxicities. As such, it is important to understand and manage these, especially in pHGG patients. Expert Opinion: Adequate integration of these considerations should allow us to effectively gain insights on biological activity, safety, and biomarkers associated with benefits for patients.